Teknik Penelusuran Analisis Data Kuantitatif dalam Penelitian Kependidikan - Rohmad Qomari (Fakultas Tarbiyah dan Ilmu Keguruan IAIN Purwokerto, 2015)
In a research process with quantitative paradigm, the important step after data have been collected is running data analysis. There are four main considerations in search appropriate analysis technique, namely problem characteristic, data scale, sample used, variable amount, and their relationship. Careful consideration is needed in order that chosen analysis technique able to answer the problem questioned.